2024
DOI: 10.1021/acsomega.3c09335
|View full text |Cite
|
Sign up to set email alerts
|

New Triazole-Based Potent Inhibitors of Human Factor XIIa as Anticoagulants

Ma’Lik D. Woodland,
Anthony Thompson,
Amanda Lipford
et al.

Abstract: Factor XIIa (FXIIa) functions as a plasma serine protease within the contact activation pathway. Various animal models have indicated a substantial role for FXIIa in thromboembolic diseases. Interestingly, individuals and animals with FXII deficiency seem to maintain normal hemostasis. Consequently, inhibiting FXIIa could potentially offer a viable therapeutic approach for achieving effective and safer anticoagulation without the bleeding risks associated with the existing anticoagulants. Despite the potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 54 publications
0
0
0
Order By: Relevance
“…To further evaluate the selectivity as well as the potential toxicity of inhibitors, we studied their effects on the clotting times of normal human plasma as well as their effects on the proliferation of three cell lines. On the one hand, the inhibitors’ effects on activated partial thromboplastin time (APTT) and prothrombin time (PT) were measured, as described earlier under in vitro conditions, using variable concentrations (0–2000 μM) (Table ). Results indicated that the inhibitors’ concentrations estimated to double APTT and PT are in the high micromolar range.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To further evaluate the selectivity as well as the potential toxicity of inhibitors, we studied their effects on the clotting times of normal human plasma as well as their effects on the proliferation of three cell lines. On the one hand, the inhibitors’ effects on activated partial thromboplastin time (APTT) and prothrombin time (PT) were measured, as described earlier under in vitro conditions, using variable concentrations (0–2000 μM) (Table ). Results indicated that the inhibitors’ concentrations estimated to double APTT and PT are in the high micromolar range.…”
Section: Resultsmentioning
confidence: 99%
“…Clotting times, including activated partial thromboplastin time (APTT) and prothrombin time (PT), were assessed in normal human plasma utilizing the BBL Fibrosystem fibrometer from Becton–Dickinson, as detailed in previous publications. For the PT assay, thromboplastin-D was dissolved in 4 mL of highly purified water and then warmed to 37 °C. Subsequently, 10 μL of the inhibitor was added to 90 μL of normal human plasma and incubated for 30 s. Following this, 200 μL of prewarmed PT reagent was added, and the clotting time was recorded.…”
Section: Methodsmentioning
confidence: 99%